Simplify the first trigonometric expression by writing the simplified form in terms of the second expression (1/1-cosx)-(cos/1+cos);cscx

Respuesta :

[tex](\frac{1}{1-cos(x)})-(\frac{cos(x)}{1+cos(x)})[/tex]

cscx is  1/sinx

maybe they want us to use pythagorean identity

[tex]cos^2(x)+sin^2(x)=1[/tex]

I notice we have 1-cos(x) and 1+cos(x), if we multiply them, we get [tex]1-cos^2(x)[/tex]

and if we look at the pythagorean identity and minus cos^2(x) from both sides, we get

[tex]sin^2(x)=1-cos^2(x)[/tex]

since [tex]csc(x)=\frac{1}{sin(x)}[/tex], [tex]csc^2(x)=\frac{1}{sin^2(x)}=\frac{1}{1-cos^2(x)}[/tex]

(recall that (a-b)(a+b)=a²-b²)

match the denomenators of the original fraction

multiply first fraction by [tex]\frac{1+cos(x)}{1+cos(x)}[/tex] and the 2nd by [tex]\frac{1-cos(x)}{1-cos(x)}[/tex]


[tex](\frac{1+cos(x)}{1-cos^2(x)})-(\frac{cos(x)(1-cos(x))}{1-cos^2(x)})=[/tex]

[tex]((csc^2(x))(1+cos(x)))-((csc^2(x))(cos(x)-cos^2(x)))=[/tex]

[tex]csc^2(x)+csc^2(x)cos(x)-(csc^2(x)cos(x)-csc^2(x)cos^2(x)=[/tex]

[tex]csc^2(x)+csc^2(x)cos(x)-csc^2(x)cos(x)+csc^2(x)cos^2(x)=[/tex]

[tex]csc^2(x)+csc^2(x)cos^2(x)=[/tex]

[tex]csc^2(x)(1+cos^2(x))[/tex], hmm, to get ride of those cos(x)

look to the pythagorean identity again


[tex]sin^2(x)+cos^2(x)=1[/tex], force one side into form 1+cos^2(x)

[tex]1+cos^2(x)=2-sin^2(x)[/tex], recall that since csc(x)=1/sin(x), sin(x)=1/csc(x) and sin^2(x)=1/(csc^2(x))

[tex]1+cos^2(x)=2-\frac{1}{csc^2(x)}[/tex]

subsituting


[tex]csc^2(x)(1+cos^2(x))=[/tex]

[tex](csc^2(x))(2-\frac{1}{csc^2(x)})=[/tex] distributing

[tex]2csc^2(x)-\frac{csc^2(x)}{csc^2(x)}=[/tex]

[tex]2csc^2(x)-1[/tex] is the simplified expression

Trigonometry identities are proved by using several other identities.

The simplified form of [tex]\mathbf{\frac{1}{1-\cos x}-\frac{\cos x}{1+\cos x}}[/tex] is  [tex]\mathbf{2csx^2 x - 1 }}[/tex]

The trigonometric expression is given as;

[tex]\mathbf{\frac{1}{1-\cos x}-\frac{\cos x}{1+\cos x}}[/tex]

Take LCM

[tex]\mathbf{\frac{1}{1-\cos x}-\frac{\cos x}{1+\cos x} =\frac{1 + \cos x - \cos x(1 - \cos x)}{(1 - \cos x)(1 + \cos x)} }[/tex]

Open brackets

[tex]\mathbf{\frac{1}{1-\cos x}-\frac{\cos x}{1+\cos x} =\frac{1 + \cos x - \cos x + \cos^2 x}{1 - \cos^2 x} }[/tex]

Evaluate like terms

[tex]\mathbf{\frac{1}{1-\cos x}-\frac{\cos x}{1+\cos x} =\frac{1 + \cos^2 x}{1 - \cos^2 x} }[/tex]

In trigonometry:

[tex]\mathbf{ \cos^2x = 1 - \sin^2 x}[/tex]

So, we have:

[tex]\mathbf{\frac{1}{1-\cos x}-\frac{\cos x}{1+\cos x} =\frac{1 +1 - \sin^2 x}{sin^2 x} }}[/tex]

[tex]\mathbf{\frac{1}{1-\cos x}-\frac{\cos x}{1+\cos x} =\frac{2 - \sin^2 x}{sin^2 x} }}[/tex]

Split

[tex]\mathbf{\frac{1}{1-\cos x}-\frac{\cos x}{1+\cos x} =\frac{2}{sin^2x} - \frac{\sin^2 x}{sin^2 x} }}[/tex]

[tex]\mathbf{\frac{1}{1-\cos x}-\frac{\cos x}{1+\cos x} =\frac{2}{sin^2x} - 1 }}[/tex]

The inverse of sin(x) is csc(x).

So, we have:

[tex]\mathbf{\frac{1}{1-\cos x}-\frac{\cos x}{1+\cos x} =2csx^2 x - 1 }}[/tex]

Hence, the simplified form of [tex]\mathbf{\frac{1}{1-\cos x}-\frac{\cos x}{1+\cos x}}[/tex] is  [tex]\mathbf{2csx^2 x - 1 }}[/tex]

Read more about trigonometry identities at:

https://brainly.com/question/10680548